STUDENTS OF ENGLISH DEPARTMENT LISTENING TYPES USING “MINEFIELDS” SONG - Siti Nur Jannah; Susilawati Susilawati; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2022)
Listening requires creativity in the learning process because speech from speakers will influence and be recorded directly into the human brain of terms, but not all humans can immediately recall what has been heard with various causal factors. This present research was aimed to find the types of listening song using Minefields’ song in Universitas Muhammadiyah Cirebon. This research employed descriptive qualitative research from the students assumptions. The reasercher arrange the datainto classes according to certain criteria for better analysis.Two instruments were used including: questionnaire and interview. The questionnaire was distributed to 20 students from 4 and 8 semester. And from 20 participants reasercher chose 6 students randomly were involved in the interview. The results showed that most of students listening types is extensive. Which means they are focus on listening continuously, managing large amounts of listening input. Learner listens to longer extracts and performs meaning content tasks. Most of participants said Minefields song can increase the their listening ability. Minefields song has vocabulary to improve listening skill while the students hearing minefields song. It consists of song inside the story as well as equipped with Interview.